Efficacy of a novel nematicidal seed treatment against Pratylenchus brachyurus and Heterodera glycines in soybean - Ribeiro, Daniela Roncato (2020)
The soybean cyst nematode (SCN, Heterodera glycines) and the root lesion nematode (RLN, Pratylenchus brachyurus) are among the most yield limiting pathogens of soybean (Glycine max L.) in Brazil. Combinations of control methods, including crop rotation and the use of resistant cultivars are not completely efficient and the search for novel strategies is needed. Nematicidal seed treatment is a promising and welcome option to manage nematodes. In this context, Syngenta will launch cyclobutrifluram, a novel active ingredient. Therefore, the registration of this molecule will provide a valuable tool for Brazilian growers to manage both SCN and RLN. The objectives of this study were to evaluate seed treatment effects on SCN and RLN populations and the impact on soybean yield. Furthermore, the phytotoxicity of cyclobutrifluram to soybean seeds and seedlings was also evaluated. Greenhouse and microplot trials were conducted in Holambra, São Paulo State in 3 years (from 2017 to 2019) for P. brachyurus and H. glycines. Generally, cyclobutrifluram greatly reduced the number of nematodes per grams of roots (at the rate >= 40 g active ingredient/100 kg of soybean seeds) and resulted in a yield increase of some cultivars compared to the treatment containing only abamectin (at the rate of 50 g a.i./100 kg of soybean seeds) and the check. Additionally, cyclobutrifluram did not exhibit any phytotoxicity effect to soybean seeds and seedlings and the growth of plants was similar to those of the untreated plants. Based on these studies, the novel nematicidal seed treatment has the potential to control both SCN and RLN populations in soybean fields in Brazil, without the risk of phytotoxicity.